1967년 민족기록화 사업과 〈구월산지구 유격대〉 연구 - 강민기(Kang, Mingi) (한국학(구 정신문화연구), 2024)
민족기록화는 박정희(朴正熙, 1917~1979) 대통령의 집권 2기(제6대 대통령, 1967~1971)에 국가 주도 문화예술정책을 대표하는 사업으로 시작되었다. 민족의 역사를 이어 온 조상들의 굳건한 자주정신과 민족적 슬기를 되새기기 위한 목적에서 기록하고 전승하기 위해 제작된 것이다. 한국학중앙연구원에는 총 12점의 민족기록화가 소장되어 있으며 선사시대 <반구대 풍요제>부터 한국전쟁기 <구월산지구 유격대>까지 긴 시기에 걸친 역사적 기록을 담고 있다. 이 연구는 ‘1960-70년대 한국의 국가와 미술: 민족기록화의 현황과 제작과정을 중심으로’라는 주제로 2024년 한국학중앙연구원의 한국학기초연구 공동연구로 진행되었다. 그중 민족기록화 사업의 첫 해에 제작된 <구월산지구 유격대>는 한국전쟁기에 황해도 구월산(九月山)을 거점으로 활동했던 김종벽(金宗璧, 1914~2004) 대위와 그 대원들의 전투 장면을 그린 1000호의 대작이다. 화가 김서봉이 37세의 비교적 젊은 나이에 추상계열의 작가로서 구상화 제작에 참여한 사실과 구월산 유격대에 관한 서사가 풍부한 작품이어서 관심을 갖게 되었다. 1967년에 제작된 민족기록화는 한국현대미술사에서 기념비적인 국가 주도 미술사업으로 시작되었지만 아쉽게도 남아 있는 관련 자료가 거의 없어 연구하는 데 어려움이 많다. 한국학중앙연구원에 소장된 2점을 제외하면 모두 산실되어 현존 여부를 알 수도 없어서 당시 발행된 그림엽서로 대부분의 작품을 확인하는 정도이다. 따라서 후대의 자료지만 한국문화예술위원회(당시 한국문화예술진흥회)의 행정 서류를 현장조사하여 민족기록화의 역사적 정황을 되짚어 보아야 할 듯하다. 기존 연구에 더하여 최초의 기획자였던 김종필의 구상, 진행 과정을 살피고, 김서봉의 <구월산지구 유격대>를 통해 민족기록화를 대하는 작가들의 기억과 소명감을 알아본다. Korean Heritage Painting is considered a representative example of the stateled cultural and artistic policies during President Park Chung-hee’s second term in office. The Academy of Korean Studies houses a total of 12 Korean Heritage Paintings, among which Guwolsan District Guerrilla Unit, painted in the first year of the Korean Heritage Painting Project, is a significant masterpiece. It depicts the battle scenes of Captain Kim Jong-byeok and his unit, who operated from Mount Guwolsan in Hwanghae Province during the Korean War. The artist who painted this work, Kim Seo-bong, is noteworthy for having created realistic record paintings despite being an artist who had previously worked on abstract art at a young age. The painting also draws attention for its rich narrative about the Guwolsan Guerrilla Unit. Korean Heritage Paintings project, initiated in 1967 as a monumental state-led art initiative in the history of modern Korean art, regrettably has only two surviving pieces out of the original 55 works. This study aims to, first, examine the role of Kim Jong-pil in the National Record Painting project, as well as its purpose and objectives. Second, it seeks to explore the historical significance of the project by analyzing Guwolsan District Guerrilla Unit by Kim Seo-bong, focusing on the selection of the artist, the choice of subject matter, and the sense of mission held by the participating artists. KCI Citation Count: 0